HASIL BELAJAR PESERTA DIDIK KELAS XI MIPA SMAN 4 BANJARMASIN PADA PEMBELAJARAN KONSEP SISTEM KOORDINASI PADA MANUSIA - Anshari, Muhammad Ridha; Noorhidayati, Noorhidayati; Amintarti, Sri (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
The application of the Problem-Based Learning (PBL) model in biology learning is relevant to the goals of 21st-century learning. The concept of Coordinating Systems in Humans must be known and understood by everyone, especially students. This study aims to describe the effect of applying the PBL model to the learning of the Coordinating System concept on the learning outcomes of students in class XI MIPA at Senior hight school  4 Banjarmasin. This study used a quasi-experimental method with the nonequivalent control group research design. The research sample was class XI MIPA 2 as the experimental class and class XI MIPA 4 as the control class for 2 meetings. The research data were obtained from the results of the pretest and posttest, LKPD. Data analysis used the Wilcoxon Signed Ranks Test at α = 0.05. The results showed (1) the application of the PBL learning model to learning the Coordination System concept in Humans had a significant effect on the learning outcomes of class XI MIPA 4 SMAN 4 Banjarmasin (2) Cognitive learning outcomes were in a good category (3) Affective learning outcomes of character behavior and social behavior are included in the good to very good category (4) psychomotor learning outcomes are good to very good category.